Determining the loading of a container for grain transportation under operating conditions - Lovska, Alyona; Karimova, Nurlana (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the processes of perception and redistribution of loads in the structure of a container for grain transportation under operating conditions. The task to address is to provide the railroad industry with vehicles for grain transportation by modernizing universal containers. To upgrade the universal container for grain transportation, a 1CC container was selected as a prototype. In order to adapt this container for grain transportation, it is proposed to install three standard-diameter loading hatches on the roof. It is planned to make an unloading hatch in the end wall 1/3 of the height of the lower strapping. To substantiate the proposed solution, the strength of the container was calculated under the following loading scenarios: transporting the container as part of a railroad train; lifting by the upper corner fittings; unloading the container. The calculation results showed that the strength of the container is ensured under all the considered loading schemes. A special feature of the results is that the provision of the railroad industry with vehicles for grain transportation is achieved not by designing new structures but by modernizing existing ones. The field of practical application of the research results is railroad transport. The conditions for the practical use of the results are the application of low-alloy steel to fabricate the components of the container structure. The results of the study will help compile recommendations for the modernization and design of container structures, as well as to improve the efficiency of container transportation, including international traffic